Ethical and unethical methods of plagiarism prevention in academic writing - Bakhtiyari, K.; Salehi, H.; Embi, M.A.; Shakiba, M.; Zavvari, A.; Shahbazi-Moghadam, M.; Ale Ebrahim, N.; Mohammadjafari, M. (Canadian Center of Science and Education, 2014)
This paper discusses plagiarism origins, and the ethical solutions to prevent it. It also reviews some unethical approaches, which may be used to decrease the plagiarism rate in academic writings. We propose eight ethical techniques to avoid unconscious and accidental plagiarism in manuscripts without using online systems such as Turnitin and/or iThenticate for cross checking and plagiarism detection. The efficiency of the proposed techniques is evaluated on five different texts using students individually. After application of the techniques on the texts, they were checked by Turnitin to produce the plagiarism and similarity report. At the end, the "effective factor" of each method has been compared with each other; and the best result went to a hybrid combination of all techniques to avoid plagiarism. The hybrid of ethical methods decreased the plagiarism rate reported by Turnitin from nearly 100 to the average of 8.4 on 5 manuscripts.